Sella turcica bridging and ossified carotico-clinoid ligament: Correlation with sex and age. Issue 3 (June 2018) - Gibelli, Daniele; Cellina, Michaela; Gibelli, Stefano; Panzeri, Marta; Oliva, Antonio Giancarlo; Termine, Giovanni; Sforza, Chiarella
Aim: Sella turcica bridging and ossified carotico-clinoid ligament are two variants of the sella turcica, the origin of which is partially unknown. These variations should be properly recognised, as they may hamper the removal of the anterior clinoid process in surgical procedures. Therefore, our aim was to determine the prevalence of these two anatomical variants and to investigate their prevalence according to patient sex and age in a series of maxilla computed tomography scans. Materials and methods: We revised 300 computed tomography scans of the head from northern Italian patients, stratified into three age groups (18–40 years, 41–60 years, >60 years): a logistic regression analysis was used to explore an association of sella turcica bridging with age and sex through Matlab software, also including a test for the extracted model ( P  < 0.05). Results: The mean prevalence of sella turcica bridging and ossified carotico-clinoid ligament were 0.16 ± 0.06 (48/300, 16.0%) and 0.09 ± 0.03 (26/300, 8.7%), respectively. Statistically significant differences according to sex were found neither for sella turcica bridging ( P  = 0.345) nor for ossified carotico-clinoid ligament ( P  = 0.412). Only sella turcica bridging showed a correlation with age ( P  = 0.007). In addition, the two variants were often associated, as patients without sella turcica bridging usually did not show ossified carotico-clinoid ligament ( P  < 0.001). Discussion: Our results suggest an association between the two variants, and provide a novel contribution to the debate around their origin.